LANDSCAPE COMPOSITIONS BASED ON EVERGREEN SHRUBS IN THE LANDSCAPING OF CITY STREETS (Conferencea, 2023)
Today, one of the main problems in urban planning is the organization of landscaping work on a scientific basis. Landscaping of residential areas - cities, districts, villages and towns - is one of the main means of improving these places. The landscaping scale indicates the culture of the population. Demographic studies show that people settle in green areas, and migration from these areas is rare. All over the world, gabions are used as barriers in European countries such as Germany, France and Italy.